Truth and Reconcilition Commissions and Health Care System Responses for Indigenous Peoples: A Scoping Review - Sarah Larson; Cortez Standing Bear; Devon Olson; Nicole Redvers (Harvard FXB Center for Health and Human Rights, 2024)
Grounded in human rights approaches, truth and reconciliation commissions (TRCs) explore an event or process that did widespread and systematic intentional harm to a group of people. Health as a fundamental right is an important component addressed by TRCs. Yet despite TRCs often having recommendations for health care systems, it is unknown how well these recommendations are being translated within health care settings. Therefore, the overarching purpose of our scoping review was to identify academic articles that discussed health care system discourse or responses to TRCs in the context of Indigenous Peoples. Our thematic analysis of the included articles identified three main themes for health care system responses to TRCs: (1) the acknowledgment of multiple ways of knowing, being, and doing in health systems; (2) current interventions as responses within health systems; and (3) suggestions for change within health systems. Although a TRC may create a specific road map and mandate for health care systems, we found considerable variability in the uptake of these actions across institutions. Concerted efforts within and around health care systems and across sectors are therefore necessary to achieve large-scale, meaningful change for Indigenous Peoples post-TRCs and to maintain accountability as a foundational human rights principle.